Bioelectrical impedance analysis and change disability post physiotherapy for patients with lower back pain attending rehabilitation care unit in Erbil - Aldhahi, Reem Burkan; Qader Omer , Dler; Rahman Sulaiman, Sherwan (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Determining the relationship between body compartments and Lower Back Pain (LBP) will increase our understanding about how body compartments can affect LBP disability. This study aimed to assess the association between body compartments and LBP disability pre and post-physiotherapy. Methods: A prospective study conducted in the main two governmental physiotherapy departments in Erbil. One Hundred patients were diagnosed with LBP and referred to physiotherapy units. All patients were assessed before starting physiotherapy and body compartments were measured by bioelectrical impedance analysis (BEIA). LBP disability was measured for each patient by a modified Oswestry disability index (ODI). After completing six sessions of physiotherapy all patients were reassessed regarding body composition, obesity measures, and LBP disability. Results: Regarding the body fat percentage (BFP), 61% of females and 56.7% of males were obese. Results showed a positive significant correlation (P = 0.013) between BFP and LBP disability after physiotherapy, while a negative significant correlation (P = 0.026) between total body water (TBW) and LBP disability. There was a significant improvement in disability after physiotherapy (P <0.001). Eleven percent of patients succeeded to reach minimal clinically important difference (MCID ≥ 30%). Body composition and other obesity measurements were not significantly different before and after physiotherapy. Conclusions: LBP disability is positively associated with BFP and negatively associated with TBW. The physiotherapy protocol performed in the physiotherapy units was able to significantly improve disability although a low number of patients reached MCID ≥ 30%. Body compartments were not significantly different before and after physiotherapy.